A high-toughness controllable-degradation low-alloyed Mg-Bi series wrought magnesium alloy and a preparation method thereof
By synergistically regulating the Mg-Bi-Sn-Mn-Ca matrix with microalloying elements Zn and Al, the problems of high cost and unstable degradation rate of existing magnesium alloys are solved, and the controllable adjustment of strength, toughness and degradation rate over a wide range is achieved, making it suitable for biodegradable downhole tools.
Patent Information
- Application Number
- CN202611562204.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-10-10
- Publication Date
- 2026-11-06
AI Technical Summary
Existing biodegradable magnesium alloy technologies suffer from high costs, complex smelting processes, and degradation rates that are sensitive to composition and processes, making it difficult to control stably and predictably over a wide range. Furthermore, they do not address the degradation behavior of non-rare earth Mg-Bi alloys.
Using Mg-Bi-Sn-Mn-Ca as the matrix, and through the individual or combined addition of microalloying elements Zn and Al and the synergistic control of extrusion temperature, the total amount of alloying elements added does not exceed 2.5 wt.%, and it is free of rare earth elements and Ni/Cu, thus achieving a wide range of control over strength, toughness and degradation rate.
It achieves high strength and toughness of the alloy and stable and predictable control of degradation rate over a wide range. The degradation rate can be set as needed within the range of 7.66 mm/y to 55.24 mm/y, which is suitable for different service conditions, reduces raw material costs and smelting process.
Smart Images

Figure CN123043385A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of metallic materials and their processing technology, specifically relating to a high-strength, tough, controllable degradable low-alloyed Mg-Bi wrought magnesium alloy and its preparation method. Background Technology
[0002] Magnesium is one of the structural metals with the lowest standard electrode potential and the highest chemical reactivity among engineering metals. In the presence of Cl... - Magnesium alloys undergo continuous matrix dissolution and hydrogen evolution reactions in aqueous environments. This characteristic makes magnesium alloys an ideal matrix for biodegradable functional structural materials, offering unique application value in oil and gas extraction and other fields. In staged fracturing operations, biodegradable downhole tools such as fracturing balls, bridge plugs, and temporary plugging tools are required to possess sufficient strength to withstand high-pressure loads during the operation period and be able to self-dissolve in the well fluid environment after the operation, eliminating the need for drilling and recycling processes, thereby shortening the operation cycle and reducing costs. The core requirements for materials in such applications are: high strength and sufficient plasticity during the service life to ensure processing and service reliability; and a moderate, stable, and predictable degradation rate after the service life, which can be adjusted within a wide range according to different operating conditions.
[0003] The existing biodegradable magnesium alloy technologies have the following shortcomings: (1) To obtain high strength, the Mg-RE (rare earth) high alloying route is often adopted, which has high raw material costs, high melting difficulty, and high deformation resistance, which is not conducive to extrusion forming and large-scale production; (2) To accelerate degradation, microcouples are often constructed by adding cathodic elements such as Ni and Cu, but the degradation rate of such alloys is often highly sensitive to composition fluctuations and processing technology, with large fluctuations in degradation rate between batches and within the process window, poor service reliability, and difficulty in independently controlling strength and degradation rate; (3) Low alloyed Mg-Bi alloys have the characteristics of low raw material costs and good thermal stability of the second phase, and are non-rare earth deformable magnesium alloy systems that have attracted attention in recent years. However, existing research and patents are focused on improving their strength through second phase strengthening and grain refinement, without addressing the degradation behavior of the alloy system, and have not proposed a composition and process synergistic design scheme that can stabilize the degradation rate and be controlled as needed within a wide range.
[0004] An investigation revealed that in the field of soluble / biodegradable magnesium alloys, patent application CN119710407A, "A High-Strength, High-Plasticity Soluble Magnesium Alloy and Its Preparation Method," discloses a Mg-Zn-Y-Ni-Cu-Zr system soluble magnesium alloy (Zn 3 wt.%~8 wt.%, Y 0.5 wt.%~2.5 wt.%, Ni 0.1 wt.%~2 wt.%, Cu 0.1 wt.%~2 wt.%), used as a temporary plugging tool in shale gas extraction. Its strength is improved by the formation of I and W phases by Zn and Y, and dissolution is accelerated by the precipitation of high-potential phases by Ni and Cu. The dissolution rate is controlled by changing the Ni and Cu content. However, this alloy has a high total element content, contains rare earth Y, Ni, and Cu, resulting in high cost and requiring a solution treatment and aging process. Controlling its dissolution rate depends on changing the content of the main alloying elements, i.e., altering the alloy's composition system. Patent CN105950930A, "A Soluble Extruded Magnesium Alloy and Its Preparation Method", discloses a soluble magnesium alloy containing Al 5 wt.%~10 wt.%, Zn 1 wt.%~3 wt.%, Ni 0.5 wt.%~3 wt.%, Cu 0.5 wt.%~3 wt.%, with the balance being Mg. It can be used to process sealing tools for fracturing in oil and gas fields and dissolves on its own after use. However, it has a high total amount of alloying elements, contains Ni and Cu, has a high cost, and has a complex smelting process. In the field of non-rare earth Mg-Bi magnesium alloys, patent CN105132772A, "A Low-Cost Non-Rare Earth High-Strength Magnesium Alloy and Its Preparation Method," discloses a Mg-Bi-Ca-Mn alloy (Bi 2 wt.%~10 wt.%, Ca 0.1 wt.%~1.5 wt.%, Mn 0.1 wt.%~1.0 wt.%, with the balance being Mg), which achieves high strength by pinning grain boundaries through the Mg-Bi second phase; patent CN105154733A, "A Novel Non-Rare Earth Cast Magnesium Alloy and Its Preparation Method," discloses a Mg-Bi-Zr-Zn casting alloy (Bi 0.5 wt.%~8 wt.%, Zr 0.35 wt.%~1.0 wt.%, Zn 0.1 wt.%~2.0 wt.%, with the balance being Mg), which utilizes Zr to refine grains and Zn for solid solution strengthening to improve as-cast strength.
[0005] In summary, existing technologies for soluble magnesium alloys largely rely on high alloying and rare earth elements such as Ni and Cu, resulting in high costs, complex smelting processes, and degradation rates that are highly sensitive to composition and processing, exhibiting poor predictability. Research on non-rare earth Mg-Bi magnesium alloys focuses on improving strength, neglecting the degradation or corrosion behavior of the alloys, and failing to propose a technical solution for achieving a wide-range controllable degradation rate through the synergy of microalloying elements and extrusion temperature. Furthermore, their compositions do not contain Sn, and their Bi content is either higher than that of this invention (e.g., Bi in CN105132772A is 2 wt.%~10 wt.%), or they introduce Zr, an element not present in this invention. Therefore, existing technologies lack a low-alloy Mg-Bi wrought magnesium alloy and its preparation method that is simple in composition, free of rare earth elements, Ni, and Cu, maintains high strength and toughness, and allows for stable and predictably controllable degradation rates over a wide range. This is precisely the technical problem this invention aims to solve. Summary of the Invention
[0006] To address the aforementioned problems in existing technologies, the present invention aims to provide a high-strength, high-toughness, controllable degradable low-alloyed Mg-Bi wrought magnesium alloy and its preparation method. Using Mg-Bi-Sn-Mn-Ca as the matrix, this invention achieves high strength and toughness with adjustable degradation rate over a wide range by synergistically controlling the addition of microalloying elements (Zn and Al, individually or in combination) and extrusion temperature, provided the total alloy element addition does not exceed 2.5 wt.% and the alloy is free of rare earth elements and Ni / Cu. With a degradation rate of 15 mm / y as the boundary, alloys with combined Zn and Al additions belong to the first degradation rate range, exhibiting a low degradation rate that is insensitive to extrusion temperature and is stable and predictable, suitable for applications requiring high predictability of degradation life. Alloys with Zn or Al added alone belong to the second degradation rate range, exhibiting a higher degradation rate that can be adjusted by extrusion temperature, suitable for applications requiring faster degradation. The combination of these two ranges with extrusion temperature control allows the degradation rate of this alloy system to be set within a wide range according to service conditions.
[0007] To achieve the above objectives, the present invention adopts the following technical solution:
[0008] A high-strength, high-toughness, controllable degradable low-alloy Mg-Bi wrought magnesium alloy is a Sn-containing, low-Bi Mg-Bi-Sn-Mn-Ca wrought magnesium alloy. By mass percentage, its chemical composition is: Bi 0.8%~1.2%, Sn 0.3%~0.5%, Mn 0.15%~0.25%, Ca 0.05%~0.15%, Zn 0%~0.3%, Al 0%~0.15%, and at least one of Zn and Al has a content that is not zero, with the balance being Mg and unavoidable impurities.
[0009] Preferably, the alloy contains both Zn and Al, with Zn accounting for 0.1% to 0.3% and Al accounting for 0.05% to 0.15% by mass percentage; more preferably, Zn accounts for 0.18% and Al accounts for 0.09%. This preferred composition exhibits high strength and toughness during extrusion at 200°C and has the lowest and most stable degradation rate at all extrusion temperatures.
[0010] The roles and proportions of each alloying element in this invention are based on the following:
[0011] Bi forms a thermally stable second phase with Mg and Ca, but it is not easily completely dissolved during homogenization and hot extrusion. In this invention, Bi is controlled in a low range of 0.8% to 1.2%. If the content is too low, the amount of the second phase will be insufficient; if it is too high, coarse second phases will easily form, which will worsen the plasticity.
[0012] Sn: Sn is one of the key additive elements that distinguishes this invention from existing Mg-Bi alloys. Sn has a certain solid solubility in Mg, and some Sn dissolves in the magnesium matrix to produce solid solution strengthening. It can also work synergistically with solute atoms in the matrix to reduce dendrite segregation in the as-cast structure, improve the compositional and microstructure uniformity of the alloy after homogenization treatment, and provide a uniform initial structure for subsequent hot extrusion. At the same time, the dissolved Sn atoms can enhance the work hardening ability of the alloy through interaction with dislocations, which is beneficial to improving the balance between strength and plasticity. In addition, the addition of Sn helps to reduce the electrochemical inhomogeneity of the matrix, inhibits the tendency of localized corrosion, and allows the alloy to undergo matrix dissolution in a more uniform manner, which is one of the compositional bases for the stable and predictable degradation behavior of the alloy in this invention. When the Sn content is too low, the above-mentioned solid solution strengthening and homogenization effects are insufficient; when the content is too high, it is easy to form coarse Sn-containing second phases, which will worsen the plasticity and become the initiation site of localized corrosion. Therefore, this invention controls Sn at 0.3%~0.5%.
[0013] Mn: Purifies the melt, removes harmful impurities such as Fe, and avoids uncontrollable accelerated corrosion caused by Fe impurities. It is the basis for ensuring a stable and predictable alloy degradation rate and also has the function of refining the microstructure. The concentration should be controlled between 0.15% and 0.25%.
[0014] Ca: It forms a second phase with Mg and Bi, and weakens the basal texture. Excessive Ca content will form too many coarse second phases, impairing plasticity and inducing localized corrosion, so it should be controlled at 0.05%~0.15%.
[0015] Zn: Trace amounts of Zn dissolve in the magnesium matrix, resulting in solid solution strengthening, which helps improve the yield strength of the alloy. When the Zn content is too low, this effect is not significant; when the content is too high, it easily impairs plasticity. Therefore, the Zn content should be controlled between 0% and 0.3%, with 0.1% to 0.3% being preferred when added.
[0016] Al can significantly reduce the content of the second phase in homogenized alloys, improving the uniformity of alloy microstructure and composition; it can also reduce the grain size of extruded alloys, especially at higher extrusion temperatures. However, excessive content can lead to the formation of an Al-containing second phase and impair plasticity. Therefore, the Al content should be controlled between 0% and 0.15%, with 0.05% to 0.15% being preferred.
[0017] The core of this invention lies in using Mg-Bi-Sn-Mn-Ca as a matrix and determining the degradation rate levels by the inclusion or exclusion of microalloying elements. This invention divides the alloy into a first degradation rate level and a second degradation rate level, using a degradation rate of 15 mm / y measured by the hydrogen evolution method in a 3.5 wt.% NaCl solution as the boundary: degradation rates below 15 mm / y belong to the first degradation rate level, and degradation rates above 15 mm / y belong to the second degradation rate level. When Zn and Al are added in combination, the degradation rate of the alloy in the first degradation rate level is approximately 7.66 mm / y to 9.30 mm / y; when only one of Zn and Al is added, the degradation rate of the alloy in the second degradation rate level is approximately 16.96 mm / y to 55.24 mm / y. The boundaries between the two levels are clear and do not overlap. The degradation rate within the same range was further fine-tuned by adjusting the extrusion temperature (200℃~350℃), allowing the degradation rate of the alloy system to be set according to service conditions within a wide range of approximately 7.66 mm / y to 55.24 mm / y, without altering the main alloying elements. Furthermore, the alloy with Zn and Al composite additions exhibited a stable degradation rate of 7.66 mm / y to 9.30 mm / y at all extrusion temperatures from 200℃ to 350℃, with fluctuations not exceeding 2 mm / y. This degradation rate was insensitive to extrusion temperature, and the degradation behavior was predictable. In contrast, the degradation rate of the alloy containing only a single microalloying element changed significantly with extrusion temperature, allowing for adjustment of the degradation rate within a second degradation rate range. Furthermore, the average grain size of the Zn and Al composite alloy is no greater than 5 μm at all extrusion temperatures from 200℃ to 350℃, significantly smaller than that of alloys containing only a single microalloying element at the same temperatures, maintaining fine and uniform grains throughout the entire extrusion temperature range. This fine and uniform microstructure corresponds to a reduced and stable alloy degradation rate. Simultaneously, this composite alloy exhibits excellent strength-ductility matching during extrusion at 200℃.
[0018] It should be noted that alloys with only Zn and alloys with only Al belong to the second degradation rate range. The two can be selected according to different mechanical property requirements: alloys with only Al have higher tensile strength (the ultimate tensile strength can reach 268.8 MPa when extruded at 200℃, which is the highest among all alloys), and are suitable for applications with high strength requirements; alloys with only Zn have better plasticity (the elongation after fracture can reach 20.1% when extruded at 250℃), and are suitable for applications with high plasticity or formability requirements.
[0019] This invention also provides a method for preparing the high-strength, tough, controllable degradable low-alloyed Mg-Bi wrought magnesium alloy, comprising three steps: smelting and casting, two-stage homogenization treatment, and hot extrusion. The specific operation steps are as follows:
[0020] (1) Smelting and casting: Pure Mg, pure Bi, pure Sn, pure Zn, pure Al, Mg-Ca master alloy and MnCl2 are used as raw materials. The crucible is dried and preheated, and pure Mg is added. Protective gas is introduced throughout the process. When the melt temperature reaches 720℃~740℃, Bi ingot is added. After complete melting, it is stirred. Then, the remaining alloy raw materials are added in batches and a covering agent is added. The temperature is raised to 710℃~730℃ for refining, stirring and skimming off the slag. The temperature is lowered to 700℃ and allowed to stand for 10 min~15 min. After skimming off the surface oxide scale, it is poured into a mold preheated to 180℃~220℃. After air cooling, it is demolded to obtain the ingot alloy.
[0021] (2) Two-stage homogenization treatment: The ingot alloy obtained in step (1) is kept at 400℃~450℃ for the first stage of homogenization, and then heated to 470℃~550℃ for the second stage of homogenization. After the heat preservation is completed, it is quenched by water to obtain a homogenized billet.
[0022] (3) Hot extrusion: The homogenized billet obtained in step (2) is heated together with the mold to the extrusion temperature and kept warm. The inner wall of the sleeve is coated with lubricant. Then, hot extrusion is carried out at an extrusion temperature of 200℃~350℃ with a head speed of 0.2 mm / s~0.7 mm / s and an extrusion ratio of (20~30):1. After extrusion, the billet is air-cooled to obtain a high-strength, tough, controllable degradable low-alloy Mg-Bi wrought magnesium alloy.
[0023] The protective gas in step (1) is a mixture of CO2 and SF6.
[0024] The two-stage homogenization process in step (2) is preferably a first-stage homogenization at 440℃ for 6 hours and a second-stage homogenization at 480℃ for 12 hours.
[0025] The lubricant in step (3) is a mixture of graphite and vegetable oil; the extrusion temperature is used to finely adjust the degradation rate within a predetermined composition range; for the preferred alloy with Zn / Al composite addition, the finest grains and excellent strength-plasticity matching can be obtained when extruded at 200℃.
[0026] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0027] (1) The total amount of alloying elements added does not exceed 2.5 wt.%, and it does not contain rare earth, Ni, or Cu elements. The raw material cost is low, the smelting process is simple, and the deformation resistance is small. It can be air-cooled after extrusion without the need for subsequent heat treatment processes such as solution aging, making it suitable for industrial hot extrusion production.
[0028] (2) The preferred alloy with Zn / Al composite addition has excellent strength and plasticity matching when extruded at 200℃. Its room temperature yield strength reaches 252.4 MPa, ultimate tensile strength reaches 260.4 MPa, and elongation after fracture reaches 14.6%. Compared with the matrix alloy of the same process (extruded at 200℃) (room temperature yield strength 224.5 MPa / ultimate tensile strength 240.6 MPa / elongation after fracture 14.5%), the strength is significantly improved and the plasticity is not reduced, realizing the synergistic optimization of strength and plasticity;
[0029] (3) The preferred alloy with Zn / Al composite addition has an average grain size of no more than 5 μm at each extrusion temperature from 200℃ to 350℃, which is significantly smaller than that of the alloy containing only a single microalloying element, and maintains a fine and uniform structure throughout the entire extrusion temperature range.
[0030] (4) The alloy is divided into a first degradation rate range (below 15 mm / y) and a second degradation rate range (above 15 mm / y) with a degradation rate of 15 mm / y as the boundary. By setting the range by whether or not the microalloying elements are combined, and then by finely adjusting the extrusion temperature, the degradation rate of the alloy system can be set as needed in a wide range of about 7.66 mm / y to 55.24 mm / y. When Zn and Al are added together, it belongs to the first degradation rate range (7.66 mm / y to 9.30 mm / y), and when only Zn or Al is added, it belongs to the second degradation rate range (about 16.96 mm / y to 55.24 mm / y). The two ranges are clearly defined and do not overlap. Moreover, the above adjustment does not require changing the main alloying elements of the alloy, so different design degradation life can be matched according to the service conditions.
[0031] (5) The preferred alloy with Zn / Al composite addition has a stable degradation rate of 7.66 mm / y to 9.30 mm / y throughout the extrusion temperature range of 200℃ to 350℃, with fluctuations not exceeding 2 mm / y. The degradation rate is not sensitive to the extrusion temperature, the degradation is uniform and predictable; while the degradation rate of the alloy containing only a single microalloying element changes significantly with the extrusion temperature. Based on this, the degradation rate can be adjusted within the second degradation rate range.
[0032] (6) The alloy composition of the present invention is simple and can be extruded and can be used for biodegradable downhole tools such as soluble fracturing balls, soluble bridge plugs, and temporary plugging tools, as well as other temporary components that bear load during service and degrade after service; the corresponding microalloying method and extrusion temperature can be selected according to different requirements for the rate of degradation. Attached Figure Description
[0033] Figure 1 The images show the microstructures of the extruded alloys of Examples 1 to 6 and Comparative Example 1. The first column (a1), (b1), (c1), and (d1) represents the MB-ZA alloys of Examples 1 to 4; the second column (a2), (b2), (c2), and (d2) represents the MB-Z alloy of Example 5; the third column (a3), (b3), (c3), and (d3) represents the MB-A alloy of Example 6; and the fourth column (a4), (b4), (c4), and (d4) represents the MB alloy of Comparative Example 1. From top to bottom, the letters a, b, c, and d correspond to extrusion temperatures of 200°C, 250°C, 300°C, and 350°C, respectively.
[0034] Figure 2 The room temperature tensile stress-strain curves of the extruded alloys of Examples 1 to 6 and Comparative Example 1 are shown; where (a) is the MB-ZA alloy of Examples 1 to 4, (b) is the MB-Z alloy of Example 5, (c) is the MB-A alloy of Example 6, and (d) is the MB alloy of Comparative Example 1.
[0035] Figure 3 The hydrogen evolution curves of the extruded alloys of Examples 1 to 6 and Comparative Example 1 in 3.5 wt.% NaCl solution are shown; where (a) is the MB-ZA alloy of Examples 1 to 4, (b) is the MB-Z alloy of Example 5, (c) is the MB-A alloy of Example 6, and (d) is the MB alloy of Comparative Example 1.
[0036] Figure 4 The degradation rate distribution of the extruded alloys of Examples 1 to 6 and Comparative Example 1 in 3.5 wt.% NaCl solution is shown in the figure. The figure shows the degradation rate range of the four alloys at various extrusion temperatures from 200℃ to 350℃, as well as the first and second degradation rate ranges with 15 mm / y as the boundary. Detailed Implementation
[0037] The present invention will be further described below with reference to embodiments and accompanying drawings. The following embodiments are for illustrative purposes only and are not intended to limit the scope of protection of the present invention.
[0038] Example 1
[0039] A high-strength, high-toughness, controllable degradable low-alloyed Mg-Bi wrought magnesium alloy has the following actual chemical composition (wt.%) determined by ICP: Bi 0.90, Sn 0.39, Mn 0.21, Ca 0.10, Zn 0.18, Al 0.09, with the balance being Mg and unavoidable impurities; the Zn / Al composite addition results in the first degradation rate range.
[0040] A method for preparing a high-strength, tough, controllable degradable low-alloyed Mg-Bi wrought magnesium alloy, the specific operation steps of which are as follows:
[0041] (1) Smelting and casting: High-purity Mg ingots, high-purity Bi ingots, high-purity Sn ingots, high-purity Zn ingots, high-purity Al ingots, Mg-Ca master alloy, and MnCl2 were used as raw materials. The crucible was dried and preheated to 500℃, and pure Mg was added. A mixed protective gas of CO2 and SF6 (volume ratio 100:1) was introduced throughout the process. When the melt temperature reached 730±10℃, Bi ingots were added. After complete melting, the mixture was stirred for 1 min to 2 min. Then, the remaining alloy raw materials were added in batches, and RJ-2 flux and RJ-5 flux were added as covering agents. The temperature was raised to 720±10℃ for refining, and the mixture was stirred for 6 min to 10 min and the bottom slag was skimmed off. The temperature was lowered to 700℃ and allowed to stand for 10 min to 15 min. After removing the surface oxide scale, the alloy was poured into a mold preheated to 200℃. After air cooling, the alloy was demolded to obtain a Φ60 mm × 200 mm ingot.
[0042] (2) Two-stage homogenization treatment: The ingot alloy is wrapped with aluminum foil and placed in a sand box. It is then kept at 440℃ for 6 hours in a resistance furnace, and then heated to 480℃ for 12 hours. After the heat preservation is completed, it is quickly taken out and water quenched to obtain homogenized billet.
[0043] (3) Hot extrusion: The homogenized billet is processed into a Φ50 mm×10 mm cylinder and the oxide scale is removed by grinding. It is then heated at 200℃ for 1 h in an electric resistance furnace together with the mold, pad, and sleeve. The inner wall of the sleeve is coated with a graphite + vegetable oil mixed lubricant. Hot extrusion is carried out on a 600 T four-column hydraulic press at a head speed of 0.5 mm / s, an extrusion ratio of 25:1, and an extrusion temperature of 200℃ to obtain an extruded bar with a diameter of 10 mm. After extrusion, it is air-cooled to obtain a high-strength, tough, controllable degradable low-alloyed Mg-Bi wrought magnesium alloy.
[0044] After testing, such as Figure 1As shown in (a1) and Table 1, the extruded alloy obtained in Example 1 has an average grain size of 1.1 μm and a fine and uniform microstructure; as shown in Table 2 and... Figure 2 As shown in (a), the room temperature tensile yield strength is 252.4 MPa, the ultimate tensile strength is 260.4 MPa, and the elongation after fracture is 14.6%; as shown in Table 3. Figure 3 (a) and Figure 4 As shown, the degradation rate in 3.5 wt.% NaCl solution was 9.30 mm / y by the hydrogen evolution method. The degradation rate was stable and the matrix was uniformly dissolved, with no obvious local corrosion.
[0045] Example 2
[0046] The alloy composition is the same as in Example 1, and the only difference in the preparation method is that the extrusion temperature is 250°C.
[0047] After testing, such as Figure 1 As shown in (b1) and Table 1, the average grain size of the extruded alloy is 2.1 μm, and its mechanical properties are shown in Table 2; as shown in Table 3, Figure 3 (a) and Figure 4 As shown, its degradation rate is 8.20 mm / y, which fluctuates by no more than 1 mm / y compared with Example 1, indicating that the degradation rate of this preferred alloy composition is not sensitive to extrusion temperature and the degradation life is predictable.
[0048] Example 3
[0049] The alloy composition is the same as in Example 1, and the only difference in the preparation method is that the extrusion temperature is 300°C.
[0050] After testing, such as Figure 1 (c1) and Table 1 show that the average grain size of the extruded alloy is 4.1 μm, and the mechanical properties are shown in Table 2; as shown in Table 3, Figure 3 (a) and Figure 4 As shown, its degradation rate is 7.66 mm / y, which fluctuates by no more than 2 mm / y compared with Example 1, indicating that the degradation rate of this preferred alloy composition is not sensitive to extrusion temperature and the degradation life is predictable.
[0051] Example 4
[0052] The alloy composition is the same as in Example 1, and the only difference in the preparation method is that the extrusion temperature is 350°C.
[0053] After testing, such as Figure 1 As shown in (d1) and Table 1, the average grain size of the extruded alloy is 4.6 μm, and its mechanical properties are shown in Table 2; as shown in Table 3, Figure 3 (a) and Figure 4As shown, its degradation rate was 9.30 mm / y, with a fluctuation of no more than 2 mm / y compared to Example 1. From Examples 1 to 4, it can be seen that the average grain size of the Zn / Al composite alloy was no greater than 5 μm at all extrusion temperatures from 200℃ to 350℃; its degradation rate remained stable between 7.66 mm / y and 9.30 mm / y, with a fluctuation of no more than 2 mm / y, belonging to the first degradation rate range and not sensitive to extrusion temperature.
[0054] Example 5
[0055] A high-strength, high-toughness, controllable degradable low-alloyed Mg-Bi wrought magnesium alloy has the following actual chemical composition (wt.%): Bi 0.95, Sn 0.40, Mn 0.22, Ca 0.10, Zn 0.20, with the balance being Mg and unavoidable impurities; only Zn is added, placing it in the second degradation rate range. Its preparation method is the same as in Example 1, with extrusion temperatures ranging from 200℃ to 350℃.
[0056] After testing, such as Figure 1 As shown in (a2), (b2), (c2), (d2) and Table 1, the average grain size of Example 5 is 1.8 μm to 10.9 μm; as shown in Table 2 and... Figure 2 As shown in (b), Example 5, after extrusion at 200℃, exhibited a yield strength of 227.2 MPa, an ultimate tensile strength of 232.4 MPa, and an elongation at break of 6.2%. At an extrusion temperature of 250℃, the elongation at break reached 20.1% (yield strength 187.7 MPa, ultimate tensile strength 237.7 MPa), demonstrating excellent plasticity; as shown in Table 3. Figure 3 (b) and Figure 4 As shown, its degradation rate in 3.5 wt.% NaCl solution is 25.16 mm / y to 55.24 mm / y, which belongs to the second degradation rate range. The degradation rate changes significantly with the extrusion temperature and can be adjusted within this range by adjusting the extrusion temperature. It is suitable for service scenarios that require high degradation rate and rapid dissolution.
[0057] Example 6
[0058] A high-strength, high-toughness, controllable degradable low-alloyed Mg-Bi wrought magnesium alloy has the following actual chemical composition (wt.%): Bi 1.06, Sn 0.42, Mn 0.24, Ca 0.10, Al 0.13, with the balance being Mg and unavoidable impurities; only Al is added, placing it in the second degradation rate range. Its preparation method is the same as in Example 1, with extrusion temperatures ranging from 200℃ to 350℃.
[0059] After testing, such as Figure 1As shown in (a3), (b3), (c3), (d3) and Table 1, the average grain size of Example 6 is 1.2 μm to 6.7 μm; as shown in Table 2 and... Figure 2 As shown in (c), the ultimate tensile strength of Example 6 after extrusion at 200℃ reached 268.8 MPa (yield strength 229.6 MPa, elongation after fracture 7.6%), which is the highest tensile strength among the four alloys; as shown in Table 3. Figure 3 (c) and Figure 4 As shown, its degradation rate in 3.5 wt.% NaCl solution ranges from 16.96 mm / y to 50.32 mm / y, falling within the second degradation rate range. The degradation rate changes significantly with extrusion temperature and can be adjusted within this range by regulating the extrusion temperature. Compared to the alloy with only Zn added (Example 5), the alloy with only Al added exhibits higher tensile strength. Examples 5 and 6 demonstrate that the two single microalloyed alloys, both belonging to the second degradation rate range, can be selected based on different strength or plasticity requirements: the alloy with only Al added is chosen when higher tensile strength is required, while the alloy with only Zn added is chosen when higher plasticity is required.
[0060] Comparative Example 1
[0061] A Mg-Bi matrix alloy (MB) without Zn / Al microalloying has the following actual chemical composition (wt.%): Bi 0.83, Sn 0.38, Mn 0.23, Ca 0.10, with the balance being Mg, without the addition of Zn and Al. Its preparation method is the same as in Example 1, with extrusion temperatures ranging from 200℃ to 350℃.
[0062] After testing, such as Figure 1 As shown in (a4), (b4), (c4), (d4) and Table 1, the average grain size of Comparative Example 1 is 1.6 μm to 9.4 μm; as shown in Table 2, the yield strength of Comparative Example 1 after extrusion at 200℃ is 224.5 MPa, the ultimate tensile strength is 240.6 MPa, and the elongation after fracture is 14.5%; as shown in Table 3, Figure 3 (d) and Figure 4 As shown, its degradation rate in 3.5 wt.% NaCl solution is 25.16 mm / y to 37.19 mm / y; since it is not microalloyed with Zn / Al, its degradation rate cannot enter the first degradation rate range below 15 mm / y, and it does not have the ability of the alloy of the present invention to flexibly set the degradation rate according to the composition range.
[0063] The average grain size, room temperature tensile mechanical properties, and degradation rate measured by hydrogen evolution method in 3.5 wt.% NaCl solution of the extruded alloys obtained in Examples 1-6 and Comparative Example 1 were tested respectively. The results are shown in Tables 1-3. The average grain size was obtained by statistical analysis of the microstructure of the extruded alloys; the tensile test was conducted at room temperature; and the degradation rate was calculated from the amount of hydrogen evolution over 24 hours.
[0064]
[0065]
[0066]
[0067] As can be seen from Examples 1 to 6 and Comparative Example 1 above, using Mg-Bi-Sn-Mn-Ca as the matrix, the degradation rate range is set by whether or not microalloying elements are added (with a degradation rate of 15 mm / y as the boundary, the first degradation rate range of 7.66 mm / y to 9.30 mm / y is achieved by adding Zn and Al in combination, and the second degradation rate range of approximately 16.96 mm / y to 55.24 mm / y is achieved by adding only Zn or Al, with clear boundaries and no overlap between the two ranges). Furthermore, by finely adjusting the extrusion temperature (200℃ to 350℃) within this range, the present invention can set the degradation rate of the alloy system as needed within a wide range of approximately 7.66 mm / y to 55.24 mm / y, while maintaining high strength and plasticity for each component alloy. In particular, the preferred alloy with Zn / Al in combination further achieves excellent strength-plasticity matching during extrusion at 200℃, and maintains a strength of no more than 5 mm / y at all extrusion temperatures from 200℃ to 350℃. The small μm crystal grains achieve the lowest and most stable degradation rate.
[0068] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A high-strength, high-toughness, controllable degradable low-alloyed Mg-Bi wrought magnesium alloy, characterized in that, The alloy is a low-Bi Mg-Bi-Sn-Mn-Ca wrought magnesium alloy containing Sn. Its chemical composition by mass percentage is: Bi 0.8%~1.2%, Sn 0.3%~0.5%, Mn 0.15%~0.25%, Ca 0.05%~0.15%, Zn 0%~0.3%, Al 0%~0.15%, and at least one of Zn and Al has a content that is not zero, with the balance being Mg and unavoidable impurities.
2. The high-strength, high-toughness, controllable degradable low-alloyed Mg-Bi wrought magnesium alloy according to claim 1, characterized in that, The total amount of alloying elements added in the alloy does not exceed 2.5 wt.%; the alloy does not contain rare earth elements, Ni and Cu.
3. The high-strength, high-toughness, controllable degradable low-alloyed Mg-Bi wrought magnesium alloy according to claim 1, characterized in that, The degradation rate of the alloy in 3.5 wt.% NaCl solution, measured by the hydrogen evolution method, is in the range of 7.66 mm / y to 55.24 mm / y. A degradation rate below 15 mm / y is classified as the first degradation rate range, and a rate above 15 mm / y is classified as the second degradation rate range. Specifically, when the alloy contains both Zn and Al, it belongs to the first degradation rate range; when the alloy contains only one of Zn and Al, it belongs to the second degradation rate range. Furthermore, the degradation rate of alloys belonging to the second degradation rate range can be adjusted by the extrusion temperature.
4. The high-strength, high-toughness, controllable degradable low-alloyed Mg-Bi wrought magnesium alloy according to claim 3, characterized in that, The alloy contains only one of Zn and Al, and its degradation rate is 16.96 mm / y to 55.24 mm / y. When the alloy contains Al but does not contain Zn, the ultimate tensile strength of the extruded alloy obtained at an extrusion temperature of 200°C is not less than 250 MPa. When the alloy contains Zn but does not contain Al, the elongation after fracture of the extruded alloy obtained at an extrusion temperature of 250°C is not less than 15%.
5. The high-strength, high-toughness, controllable degradable low-alloyed Mg-Bi wrought magnesium alloy according to claim 1, characterized in that, The alloy contains both Zn and Al, with Zn accounting for 0.1% to 0.3% and Al accounting for 0.05% to 0.15% by mass percentage.
6. The high-strength, high-toughness, controllable degradable low-alloyed Mg-Bi wrought magnesium alloy according to claim 5, characterized in that, The alloy belongs to the first degradation rate range, with a degradation rate of 7.66 mm / y to 9.30 mm / y. The degradation rate of the extruded alloy obtained within the extrusion temperature range of 200℃ to 350℃ fluctuates by no more than 2 mm / y, and the degradation rate is not sensitive to the extrusion temperature. The average grain size of the extruded alloy obtained within the extrusion temperature range of 200℃ to 350℃ is no greater than 5 μm. Among them, the room temperature yield strength of the extruded alloy obtained at an extrusion temperature of 200℃ is no less than 240 MPa, the ultimate tensile strength is no less than 255 MPa, and the elongation after fracture is no less than 13%.
7. A method for preparing a high-strength, tough, controllable degradable low-alloyed Mg-Bi wrought magnesium alloy according to any one of claims 1 to 6, characterized in that, Includes the following steps: Step 1, Melting and Casting: According to the composition ratio of the alloy, pure Mg, pure Bi, pure Sn, pure Zn, pure Al, Mg-Ca master alloy and MnCl2 are used as raw materials; pure Mg is melted under a protective atmosphere, and Bi is added when the melt temperature reaches 720℃~740℃ and stirred until completely melted. Then the remaining alloy raw materials are added in batches and a covering agent is added; the temperature is raised to 710℃~730℃ for refining, stirring and skimming off the slag; the temperature is lowered to 700℃ and allowed to stand for 10 min~15 min, then poured into a mold preheated to 180℃~220℃, and air-cooled to demold, to obtain the ingot alloy; Step 2, Two-stage homogenization treatment: The alloy ingot obtained in Step 1 is held at 400℃~450℃ for the first stage of homogenization, and then heated to 470℃~550℃ for the second stage of homogenization. After the holding is completed, it is water quenched to obtain a homogenized billet. Step 3, hot extrusion: The homogenized billet obtained in step 2 is heated together with the die to the extrusion temperature and kept at that temperature. The inner wall of the sleeve is coated with lubricant. Then, hot extrusion is carried out at an extrusion temperature of 200℃~350℃ with a head speed of 0.2 mm / s~0.7 mm / s and an extrusion ratio of (20~30):
1. After extrusion, the material is air-cooled to obtain a high-strength, tough, controllable degradable low-alloyed Mg-Bi wrought magnesium alloy.
8. The method for preparing high-strength, tough, controllable degradable low-alloyed Mg-Bi wrought magnesium alloy according to claim 7, characterized in that, In step one, the protective atmosphere is a mixture of SF6 and CO2; in step two, the first homogenization stage is held at 440℃ for 6 hours, and the second homogenization stage is held at 480℃ for 12 hours.
9. The preparation method according to claim 7, characterized in that, In step three, the pressure head speed is 0.5 mm / s and the extrusion ratio is 25:1; for alloys containing both Zn and Al, the extrusion temperature is 200℃.
10. The method for preparing high-strength, tough, controllable degradable low-alloyed Mg-Bi wrought magnesium alloy according to claim 7, characterized in that, The degradation rate of the alloy was determined by selecting whether to add Zn and Al simultaneously in step one, and the degradation rate of the alloy was adjusted within the specified range by adjusting the extrusion temperature in step three. This ensured that the degradation rate of the obtained high-strength, tough, controllable degradable low-alloyed Mg-Bi wrought magnesium alloy, as measured by the hydrogen evolution method in 3.5 wt.% NaCl solution, was within the range of 7.66 mm / y to 55.24 mm / y.
Citation Information
Patent Citations
Low-cost non-rare-earth type high-strength magnesium alloy and preparing method thereof
CN105132772A
Novel non-rare earth cast magnesium alloy and preparation method thereof
CN105154733A
Soluble extrusion magnesium alloy and preparation method thereof
CN105950930A
High-strength and high-plasticity soluble magnesium alloy and preparation method thereof
CN119710407A
